The risks and benefits of cyclo-oxygenase-2 inhibitors in prostate cancer: a review. - Sooriakumaran, P; Kaba, R (2005)
Cyclo-oxygenase (COX), also referred to as prostaglandin (PG) endoperoxidase synthase, is a key enzymatic mediator in the production of arachidonic acids to PGs and eicosanoids. Two isoforms of COX exist, namely COX-1 and COX-2, which have distinct physiological functions and tissue distribution. Epidemiological studies suggest that regular consumption of aspirin and/or other non-steroidal anti-inflammatory drugs (NSAIDs), which inhibit COX, could notably reduce the risk of developing many cancers. COX-2 expression has been shown to increase in many cancers and cancer cell lines, including human prostate adenocarcinoma. COX-2 may also be upregulated in proliferative inflammatory atrophy (PIA) of the prostate, a pre-neoplastic lesion. The COX-2 pathway may therefore be a useful target for chemoprevention of prostate cancer, and there is much interest in exploring this with the use of COX-2 inhibitor drugs such as celecoxib. While there is concern regarding the cardiovascular toxicities of coxibs, there is no evidence that there is any increased risk with the use of celecoxib in the short-term neoadjuvant setting.